Rancang Bangun Aplikasi Layanan Ujian Berbasis Komputer di Portal Akademik Perguruan Tinggi: Design and Development of Computer-Based Examination Services Application in Higher Education Academic Portal - Gabriel Febrian Zhilwan Sadu; Sary Diane Ekawati Paturusi; Alwin Melkie Sambul (Universitas Sam Ratulangi, 2023)
Sam Ratulangi University has several rooms equipped with computers that can be used for online exams but are rarely utilized. This study aims to develop a computer-based exam service application that provides the option for conducting exams in specific computer rooms. For the convenience of lecturers and students, the application can be integrated as a feature within the university's academic portal. Based on the research and development conducted, it can be concluded that the development of a computer-based exam service application in the Academic Portal of the University can provide numerous benefits. The MVC structure in the CodeIgniter Framework facilitates a more organized application development process. Additionally, the use of the Summernote Editor makes exam questions visually appealing and interactive. By integrating this application into the university's Academic Portal, it can support exam activities within the university and optimize the utilization of computer rooms that were previously underutilized.